DISTANCE TRAINING OF DENTAL AND ORAL THERAPIST FUNCTIONAL POSITIONS AS AN EFFORT INCREASED KNOWLEDGE OF DENTAL AND ORAL HEALTH CARE SERVICES - Ajeng Choirin; Taufik Hidayat; Aris Nugroho (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: Dental and Oral Therapist Functional Positions from CPNS formation are required to attend the training of the Dental and Oral Therapist Functional Positions first appointment in accordance with applicable regulations. Bapelkes Semarang as a training unit of the Ministry of Health held a Distance Training for 4 batches of Dental and Oral Therapists Functional Positions in 2022. The training aims to increase the knowledge of trainees in carrying out dental and oral health care. Objective: This study aims to analyze the effectiveness of Distance Training of Dental and Oral Therapist Functional Positions towards increasing the knowledge of trainees in dental and oral health care services. Methods: Quasi experimental design with the pretest-posttest one group design. The number of samples is a total population of 120 participants in the Distance Training of Dental and Oral Therapists Functional Positions in 2022. Data analysis used descriptive analysis and one-way ANOVA (Brown-Forsythe). Results: The descriptive test showed an increase in knowledge in each batch and the one-way ANOVA (Brown-Forsythe) statistical test showed a p value = 0.333 (p>0.05). It can be concluded that there is no significant difference in increasing knowledge among the four training batches. Conclusion: Distance Training of Dental and Oral Therapist Functional Positions is effectively increase the knowledge of trainees in dental and oral health care services.